Hemotropic Mycoplasmas (Hemoplasmas) in Free-Ranging Azara’s Agoutis (Dasyprocta azarae) from an Urban Area of Southern Brazil - Elshafie, Nelly O.; Kmetiuk, Louise B.; Pellizzaro, Maysa; Haisi, Amanda [UNESP]; Conrado, Francisco de O.; Weckerlin, Patricia; Ullmann, Leila S. [UNESP]; Araújo Junior, João P. [UNESP]; Messick, Joanne B.; Biondo, Alexander W.; Dos Santos, Andrea P. (Wildlife Disease Association, 2024)
Hemotropic mycoplasmas (hemoplasmas) are opportunistic bacteria that attach to the erythrocyte surface, causing infectious anemia in several mammalian species, including rodents. Studies surveying native Azara’s agoutis (Dasyprocta azarae) in Brazil are lacking. Accordingly, the present study aimed to assess hemoplasmas infection in free-ranging agoutis from an urban environmental conservation area in Curitiba, southern Brazil. Overall, 11/35 (31.43%) agoutis were positive to hemoplasmas by quantitative PCR (cycle threshold≤34.4). Sequencing of the 16S ribosomal RNA gene indicated Mycoplasma haemomuris infection, closely related to M. haemomuris subsp. ratti, suggesting hemoplasma transmission from urban rats to agoutis. Because the main route of M. haemomuris transmission has been direct rodent-to-rodent infection, the relatively lower positivity that we detected may be the result of low intraspecies contact due to the smaller social units of agoutis, generally consisting of two to four individuals, and low interspecies contact due to only sporadic agouti-rat interactions in urban settings, compared with other rodent species interactions. Further studies should be conducted to determine whether the hemoplasma infection that we found can cause clinical onset and life-threatening anemia in agoutis.
Keywords: Infectious disease; Rodentia; wild rodents; zoonosis